2007
DOI: 10.1002/mnfr.200600298
|View full text |Cite
|
Sign up to set email alerts
|

Factor VII polymorphisms influence the plasma response to diets with different fat content, in a healthy Caucasian population

Abstract: Our data show that carriers of the RR and/or A1A1 genotype present higher FVII Ag levels after the consumption of a SAT diet compared with the MEDIT and CHO rich diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Olive oil intake contributes to the homeostasis of the thrombogenic profile by improving the production of coagulation factors and biomarkers related to platelet aggregation [74]. Olive oil intake attenuates the pro-thrombotic state in the postprandial phase [75,76,77,78] and this is very likely due to the effect of hydroxytyrosol, as ad-hoc human experiments demonstrated [79]. Moreover, phenolic-rich olive oil intake also improved the postprandial pro-thrombotic state (activated coagulation factor VII, tissue plasminogen activator, tissue factor, plasminogen activator inhibitor type-1, and fibrinogen) in several randomized controlled trials in healthy subjects [80] and in hypercholesterolemic patients [74].…”
Section: Extra-virgin Olive Oils and Prevention Of Ncdsmentioning
confidence: 99%
“…Olive oil intake contributes to the homeostasis of the thrombogenic profile by improving the production of coagulation factors and biomarkers related to platelet aggregation [74]. Olive oil intake attenuates the pro-thrombotic state in the postprandial phase [75,76,77,78] and this is very likely due to the effect of hydroxytyrosol, as ad-hoc human experiments demonstrated [79]. Moreover, phenolic-rich olive oil intake also improved the postprandial pro-thrombotic state (activated coagulation factor VII, tissue plasminogen activator, tissue factor, plasminogen activator inhibitor type-1, and fibrinogen) in several randomized controlled trials in healthy subjects [80] and in hypercholesterolemic patients [74].…”
Section: Extra-virgin Olive Oils and Prevention Of Ncdsmentioning
confidence: 99%
“…Also it has been reported that, when a habitual diet high in monounsaturated fatty acid, such as the MedDiet, is consumed, a lower post-prandial increase of coagulation factor VII (FVIIc) has been reported in other studies [ 36 , 37 ]. Moreover, some genetic polymorphisms have been linked to this observation [ 38 ], showing the interest in the integration of omic data. Although those biomarkers are mainly associated with CVD, some of them may have an important role in other diseases such.…”
Section: Effects Of the Meddiet On Traditional Biomarkers (Classicmentioning
confidence: 99%